Answer:
ΔPTS≅ΔRTA by AAS axiom of congruency
Step-by-step explanation:
Consider ΔPQA and ΔRQS
∠PQA=∠RQS (Vertically Opposite Angles)
∠QAP=∠QSR (Complementary of two equal angles, ∠RAT and∠PST)
Due to angle sum property of a triangle, we come to the conclusion that
∠APQ=∠SRQ
Consider ΔPTS and ΔRTA
TA=TS (Given)
∠RAT=∠PST(Given)
∠APQ=∠SRQ (Proved above)
Therefore, ΔPTS≅ΔRTA by AAS axiom of congruency.
(2x + 3y = 12) x (-2)
(4x - 3y = 6) x 1
-4x - 6y = -24
4x - 3y = 6
You can cancel out the x values by adding the two equations together.
(-4x + 4x) + (-6y - 3y) = (-24 + 6)
-9y = -18
y = 2
Solve for x now...
4x - 3(2) = 6
4x - 6 = 6
4x = 12
x = 3
Check... (x = 3, y = 2)
2(3) + 3(2) = 12
6 + 6 = 12
12 = 12 <- this works!
4(3) - 3(2) = 6
12 - 6 = 6
6 = 6 <- this works!
Answer:
At least two of the lateral faces are congruent.
Step-by-step explanation:
Because the words "at least" are used this means that at a minimum 2 of the faces are congruent. Because the base is in the shape of a triangle, this will definitely be true.
hope this helps:)
Answer:
A.
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
2 bc 1 is 3 and your going down one so 0 is 2